Analysis of Student Job Readiness in Facing AI Transformation Towards Society 5.0 in XYZ University Students - Rahman, Aura; Lattu, Arny; Permana, M. Anton (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
This study analyzes the factors influencing job readiness among XYZ University students in the context of Society 5.0. The novelty of this research lies in its application of Soft Systems Methodology (SSM) combined with quantitative questionnaire analysis, enabling both systemic and measurable problem identification—an approach still rarely applied in studies of student job readiness in Indonesia. A survey was conducted with 355 active students across five study programs and analyzed using IBM SPSS 2.5 to ensure data reliability. The findings reveal that AI literacy, psychological readiness, and the use of digital technologies have a significant impact, while human-centered skills such as communication and empathy serve as key reinforcing factors. Practically, this study encourages universities to integrate technology-based technical skills with soft skills in their curricula and training programs to produce graduates who are more adaptive, competitive, and prepared for the demands of Society 5.0. The study’s contribution lies in its use of SSM to map complex issues and formulate strategies for improving job readiness. The implication is that universities should embed technical competencies, soft skills, and AI-based training into adaptive learning ecosystems to better prepare graduates for the challenges of Society 5.0.